Synthesis and characterization of new interpenetrated hydrogels from N-isopropylacrylamide, 2-oxazoline macromonomer and acrylamide. (15th August 2022) - Rengifo, Joel; Zschoche, Stefan; Voit, Brigitte; Carlos Rueda, Juan
Graphical abstract: Highlights: For the first time, an IPN hydrogel between PNiPAAm and a graft copolymer of PAAm with pH sensitive POx side chain is reported. Temperature-sensitivity is retained but dependent on composition whereas pH sensitivity is independent from composition. H-bonding between AAm and COOH units controls the swelling behavior. The IPNs are mechanically very stable and show a swelling behavior favorable for actuation. Abstract: New interpenetrated hydrogels (IPN), sensitive to pH and temperature, were synthesized by sequential free radical polymerizations in aqueous medium. In the first stage, a thermosensitive hydrogel of poly(N-isopropylacrylamide) (HG-PNiPAAm) was prepared, and in the second stage a hydrogel of acrylamide and 2-oxazoline macromonomer (MM) containing carboxylic acid ester groups was synthesized in the presence of the PNiPAAm hydrogel. In both stages, bisacrylamide was used as a crosslinker. The 2-oxazoline macromonomer was a random copolymer of methyl-3-(oxazol-2-yl)-propionate (EsterOxa) (23 % mol) and 2-methyl-2-oxazoline (MeOxa) (77 % mol) with a polymerization degree of 21 and contained a vinylbenzene end group for radical polymerization. Five different IPN-hydrogels were synthesized, the amount of the oxazoline was varied systematically, and the EsterOxa units were finally hydrolyzed to carboxylic acid groups. The structure of the IPNs was characterized by 1 H HR-MAS NMR spectroscopy. All IPN hydrogels showed a conformational transition when varying the temperature or the pH value and these transitions were a function of the composition of the IPN hydrogel. While pure HG-PNiPAAm resulted in a transition temperature of 31 °C, this value rose to 50 °C and higher for MM-H containing IPNs. This property was shown macroscopically as a contraction or expansion of the hydrogel but also in the 1 H HR-MAS NMR measurements. The sensitivity to pH in the IPN hydrogels was manifested as a contraction of the volume of the hydrogel at low pH. While introducing poly(acryl amide) PAAm increased the degree of water absorption, increasing the amount of hydrolyzed EsterOxa macromonomer within the hydrogel decreased this absorption at high pH values. These features were attributed to the formation of hydrogen bonds between the acid and amide or protonated amino groups. A lower initial swelling at elevated temperatures but constant switching pH value (pH = 6) supported this reasoning. Importantly, at 20 °C and pH = 5.7 all IPN had a similar degree of swelling Q of 34 to 39, strongly reduced due to the IPN structure compared to a PAAmMM hydrogel (Q > 200). The reported IPNs result from a straight forward synthesis and are thus an interesting material for future applications as potent actuator and sensor materials.